Electronic Storybooks: A Constructivist Approach to Improving Reading Motivation in Grade 1 Students - Ciampa, Katia (Canadian Journal of Education/Revue canadienne de l’éducation, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> This study stemmed from a concern of the perceived decline in students’ reading motivation after the early years of schooling. This research investigated the effectiveness of online eBooks on eight grade 1 students’ reading motivation. Eight students were given ten 25-minute sessions with the software programs over 15 weeks. Qualitative data were collected from students, teachers, and parents through questionnaires, interviews, observations and field notes. The results suggest the promise of online reading software programs in supporting early readers with reading, motivation, and/or behavioural difficulties. Keywords: digital reading; early literacy; reading motivation; online; eBooks; constructivism